Design and analysis of piezoelectric micromachined ultrasonic transducer using high coupling PMN-PT single crystal thin film for ultrasound imaging. (26th March 2021) - Chen, Mingzhu; Zhang, Qiaozhen; Zhao, Xiangyong; Wang, Feifei; Liu, Huiling; Li, Baichuan; Zhang, Xiangfen; Luo, Haosu
Abstract: Due to its higher frequency, improved impedance matching, and easy formation of array, piezoelectric micromachined ultrasonic transducer (PMUT) has drawn much attentions for application in ultrasound imaging. In this paper, PMUT based on [011] poled 0.70Pb(Mg1/3 Nb2/3 )O3 –0.30PbTiO3 (PMN-0.30PT) single crystal thin film was proposed and modeled by performing finite element method. Influences of different configurations of top electrode shape and bottom cavity shape on PMUT performance were studied. The investigation results show that the resonant frequency of PMN-PT-based PMUT with circular top electrode and square bottom cavity is up to 27.155 MHz. The effective electromechanical coupling coefficient ( k eff 2 ) of PMUT was up to 2.32%, which was 127% larger than that of lead zirconate titanate-based PMUT. The static transmitting sensitivity was three times enhancement compared to PMUT with square top electrode and square bottom cavity. Furthermore, acoustic field characteristics of PMUT and PMUT arrays based on PMN-PT in water were investigated. The relative pulse-echo sensitivity level of 2 × 2 PMUT array was −35 dB with the reflector at 200 μ m. The obtained results demonstrated that the proposed PMN-PT-based PMUT can achieve high frequency and large k eff 2 as well as considerable sensitivity, which is promising for application in high resolution ultrasound imaging.